Thin Films for Organic-based Optoelectronics: Chemical and Physical Characterization using Atomic Force Microscopy and Tools for Sub-molecular Level Structure Information - Liiro Peluso, Letizia (2023)
The tendency of organic compounds to form supramolecular arrangements and defined nanostructures, when deposited in the solid state as thin films, has been widely implemented in organic electronic devices for sustainable energy generation. A key feature in such systems is the strong connection between their performance and the morphology of the bi-continuous interpenetrating network, known as the active layer (AL). The organic materials involved are extremely sensitive to the experimental conditions, such as the choice of solvent, spin coating procedure and drying rates, post-deposition annealing process, component ratio, type of substrate. Intermittent contact-mode atomic force microscopy (AC-mode AFM), in some cases performed with higher eigenmodes, has proven to be a powerful technique to acquire real space images of organic-based nanometric thick films. The morphology of the top layer of a coated film is often resolved at the scale of hundreds of nanometres but fine details of the domains and the order within them can be difficult to identify. Here, the investigation of these systems combines AC-mode AFM with a variety of solid-state techniques depending on the physico-chemical properties to explore and on the response of the organic films. Analysis of the “standard” AL made of the P3HT polymer and a fullerene derivate (PCBM), spin coated on a bulk heterojunction (BHJ) solar cell architecture, has shown subtle effects on the surface morphology of P3HT:PCBM mixtures at a sub-molecular level. Firstly, a characteristic periodicity of the regioregular polymer is identified within the nanoscale domains followed by the investigation of the stoichiometric mixtures. The analysis has revealed, by AC-mode AFM, a distortion of such domains caused by the presence of the fullerene derivative. The study has contributed to the understanding of the well-known low photovoltaic performance of this blend. A BHJ architecture featuring a low bandgap polymer, known as PBDB-T-2F, and a non-fullerene small molecule (ITIC-4F) incorporated as AL is spun cast on the PEDOT:PSS/ITO-glass (anode) substrate. The AL results embedded between the PEDOT:PSS (hole transport layer) film and the PTCDI perylene derivative (electron transport layer) layer, and aluminium contacts are used as cathode. The dependence of the fine tuning of the AL surface morphology on various parameters (choice of solvent, donor:acceptor ratio, post-deposition annealing) is investigated. In addition, the 3D composition of the layered BHJ solar cell is revealed using an innovative low-impact procedure developed with electron microscopy techniques. It is proved that the non-disruptive method can be used for the characterization of materials for organic electronics. AC-mode AFM and photoluminescence studies are used to investigate the arrangement of PTCDI while a two-step process is optimised for the evaporation of the aluminium contacts. The findings are discussed, and contributions given on the characterization and manufacturing of BHJ solar cells. Chiroptically active thin films can be obtained in a variety of conditions relevant for technological applications. Combination of achiral polymers with small quantities of a chiral small molecule additive (aza[6]helicene) or AcP:CA, and intrinsically chiral sidechain polymers have shown a route to prepare films with an intense dissymmetry factor (g-factor), without the need of an alignment layer, and at compatible film thickness with technological approaches. AC-mode AFM and diffraction data, circular dichroism and ellipsometry spectroscopies have shown that large chiroptical effects are caused by magneto-electric coupling, not structural chirality as previously assumed, and, for AcP:CA, occurs due to the formation of a double twist cylinder blue phase-type 3D organization. Films made of a dissymmetric diketopyrrolopyrrole derivative (BDPP) that absorb and emit circularly polarized light may be promising for optoelectronic advances. AC-mode AFM and spatially resolved circular dichroism imaging, performed at the Beamline B23, Diamond Light Source (UK), are used to investigate spin coated films, in the pure form and as a blend with a non-fullerene small molecule (ITIC-4F). The blend films have shown a decrease in optical activity with respect to the single component counterparts. When the films are annealed or the solutions heat-treated, the corresponding films showed a local increment of the chiroptical response. In addition, investigation of different BDPP:ITIC-4F ratios, and the impact of various substrates interfaces have revealed subtle differences in the sub-micron morphological organization of the films while the acquisition of optical micrographs has shown that the chiral single component films formed spherulites while the blends are characterized by twisted crystals (in some cases). Overall, this thesis has contributed to the field of optoelectronic applications by exploring the intimate nature of organic materials, with a variety of properties, when deposited in the solid state as films. The impact of their surface supramolecular arrangement, their bulk 3D structure and their spectroscopic properties are the key to understanding their functionality as part of innovative and sustainable organic electronic devices.